2022
DOI: 10.3390/medicina58121862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Diagnosis and Management of Gynecological Cancer: A Single-Center Analysis

Abstract: Background and Objectives: The COVID-19 pandemic impacted health systems worldwide, particularly cancer care. Because the actual implications of these changes on gynecological oncology healthcare are still unclear, we aim to evaluate the impact of this pandemic on the diagnosis and management of gynecological cancer. Materials and Methods: This is a single-center retrospective observational study, including patients diagnosed with gynecological malignancies between January 2019 and December 2021. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
(56 reference statements)
0
4
1
Order By: Relevance
“…This finding has important clinical implications as it highlights the adoption of SGO’s modified treatment recommendations in ovarian cancer patients during the pandemic, in the US. However, unlike Algera’s and Antunes’ studies ( 2 , 12 ), we reported the adjusted association of the COVID-19 pandemic with neoadjuvant chemotherapy. In the adjusted model, we observed that patients in the older age groups, patients diagnosed at FIGO stages III and IV, and patients with a higher comorbidity burden were more likely to receive neoadjuvant chemotherapy than their respective counterparts.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…This finding has important clinical implications as it highlights the adoption of SGO’s modified treatment recommendations in ovarian cancer patients during the pandemic, in the US. However, unlike Algera’s and Antunes’ studies ( 2 , 12 ), we reported the adjusted association of the COVID-19 pandemic with neoadjuvant chemotherapy. In the adjusted model, we observed that patients in the older age groups, patients diagnosed at FIGO stages III and IV, and patients with a higher comorbidity burden were more likely to receive neoadjuvant chemotherapy than their respective counterparts.…”
Section: Discussioncontrasting
confidence: 75%
“…Studies conducted in Europe have reported an increase in neoadjuvant chemotherapy use in ovarian cancer patients after the onset of the pandemic ( 2 , 12 ). Our findings are consistent; we observed a 29% increased use of neoadjuvant chemotherapy in patients diagnosed during the pandemic period compared to pre-pandemic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the evidence regarding the impact of COVID-19 on treatment decisions for other types of cancer remains inconclusive. While some studies report a significant reduction in the use of adjuvant therapy [ 19 ], others indicate an increase in neoadjuvant therapy options [ 20 ]. The levels of evidence in these studies are not yet sufficient and do not yet allow to draw robust conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the importance of discussing individual cases within the context of the MDT was even more crucial [ 36 ]. The pandemic led to delays between MDT discussion and treatment, with the median duration increasing from 23 days in 2019 (pre-pandemic era) to 34 and 36 days in 2020 (during the pandemic with high restrictions) and 2021 (pandemic recovery period) [ 37 ]. Despite these challenges, adhering to guidelines within an MDT framework proved essential.…”
Section: Discussionmentioning
confidence: 99%